Evaluation of the Factors which Contribute to the Ocular Complaints in Computer Users - Smita Agarwal; Dishanter Goel; Anshu Sharma (Journal of Clinical and Diagnostic Research, 2013)
ABSTRACT Context: Use of information technology hardware given new heights to professional success rate and saves time but on the other hand its harmful effect has introduced an array of health related complaints causing hazards for our human health. Increased use of computers has led to an increase in the number of patients with ocular complaints which are being grouped together as computer vision syndrome (CVS). In view of that, this study was undertaken to find out the ocular complaints and the factors contributing to occurrence of such problems in computer users. Aims: To evaluate the factors contributing to Ocular complaints in computer users in Teerthanker Mahaveer University, Moradabad, U.P. India. Settings and Design: Community-based cross-sectional study of 150 subjects who work on computer for varying period of time in Teerthanker Mahaveer University, Moradabad, Uttar Pradesh. Materials and Methods: Two hundred computer operators working in different institutes offices and bank of were selected randomly in Teerthanker Mahaveer University, Moradabad, and Uttar Pradesh. 16 were non responders 18 did not come for assessment and 16 were excluded due to complaints prior to computer use making no response rate Twenty-one did not participate in the study, making the no response rate 25%. Rest of the subjects (n = 150) were asked to fill a pre-tested questionnaire, after obtaining their verbal consent Depending on the average hours of usage in a day, they were categorized into three categories viz. <2 hrs, 2-6 hrs, >6 hrs of usage. All the responders were asked to come to the Ophthalmic OPD for further interview and assessment. Statistical Analysis Used: Simple proportions and Chi-square test. Results: Among the 150 subjects studied major ocular complaint reported in descending order were eyestrain. (53%). Occurrence of eye strain, ( 53.8%), itching ( 47.6%) and burning (66.7%) in subjects using computer for more than 6 hours. distance from computer screen with respect to eyes, use of antiglare screen, taking frequent breaks, use of LCD monitor and adjustment of brightness of monitor screen bear a significant association with these ocular complaints in computer users. Conclusions: Eye strain is the most common ocular complaints among computer users working for more than 6 hours a day. We also found that maintaining ideal distance from screen, keeping level of eyes above the top of screen, taking frequent breaks, using LCD monitors and using antiglare screen and adjusting brightness levels according to workplace reduced these ocular complaints to a significant level.